Prognostic significance of C-reactive protein/albumin and neutrophil/lymphocyte ratios in patients with COVID-19 - Polat, Hatice Beyazal; Arpa, Medeni; Polat, Zehra; Beyazal, Mehmet; Çelike, Fatma Beyazal; Ayaz, Teslime; Ertürk, Ayşe (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. COVID-19 causes an uncontrolled and generalized inflammatory response of the host immune system. Early recognition of the disease and early prediction of the clinical course are of great importance. The aim of this study was to evaluate the predictive role of the C-reactive protein/albumin ratio (CAR) and the neutrophil/lymphocyte ratio (NLR) for mortality in patients hospitalized with the diagnosis of COVID-19. Material and methods. The patients, who were hospitalized for COVID-19 and whose CRP, albumin, neutrophil, and lymphocyte levels were documented within the first 24 hours after admission, were analyzed retrospectively. Patients were divided into survivors and non-survivors; the groups were compared. Univariate and multivariate Cox regression models were developed to evaluate the CAR and the NLR as risk factors for mortality in COVID-19 patients. Results. One hundred and thirty patients were included in this study. The mean age of the survivor group (n=114) was 60±16 and 52% were male. The mean age of the non-survivor group (n=16) was 75±13 and 56% were male. In the non-survivor group, the CAR detected at the time of admission to the hospital was significantly higher compared to patients in the survivor group (p=0.026). Conclusion. As a result, the CAR, the NLR and LDH are independent risk factor indicators of mortality in hospitalized patients
This manuscript have been approved by the Internal Review Board of RTEÜ Hospital (2021/170).
Keywords: COVID-19; C-reactive protein/albumin; neutrophil/lymphocyte